Gaining in pan-affinity towards sigma 1 and sigma 2 receptors. SAR studies on arylalkylamines. Issue 1 (1st January 2017) - Rossi, Daniela; Rui, Marta; Di Giacomo, Marcello; Schepmann, Dirk; Wünsch, Bernhard; Monteleone, Stefania; Liedl, Klaus R.; Collina, Simona
Graphical abstract: Abstract: Sigma Receptor (SR) modulators are involved in different signal transduction pathways, representing important pharmacological/therapeutic tools in several pathological conditions, such as neurodegenerative diseases and cancers. To this purpose, numerous compounds have been developed in order to target selectively one of the two subtypes (S1R and S2R) as chemotherapeutic agent. However, experiments have also shown that ligands which are able to bind both SR subtypes can be useful for the diagnosis and/or the treatment of cancers. Therefore, the discovery of compounds with good affinity towards both S1R and S2R ('pan-modulators') is also of great interest and still represents a challenge up to now. For this reason, we synthesized novel arylalkylamines with the aim to obtain compounds with S1R and S2R affinity in the nM range and, by modeling quantitative structure–activity relationships (QSARs), we identified the essential structural features to obtain promising pan-compounds.